SERVICE, PROMOTION, OR CONVENIENCE? RETHINKING THE O2O MARKETING MIX AND PURCHASE INTENTION AMONG GENERATION Z CONSUMERS IN CHINA - Fang , Zhang; Mohamed, Rozita Naina; Bahtar, Azlin Zanariah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
With the continuous integration of online and offline channels, the Online-to-Offline (O2O) model has become an important retail form in emerging markets. Although the importance of the O2O model has become increasingly evident, platform managers in practice still face a key question: which dimensions of the O2O marketing mix truly influence consumers’ purchase intention? Based on the Stimulus-Organism-Response (SOR), this study focuses on Generation Z consumers in China, systematically examines the effects of different O2O marketing mix dimensions on purchase intention, and highlights the role of customer trust in this process. To empirically examine these relationships, this study collected a total of 235 valid samples through questionnaires and used the partial least squares structural equation model (PLS-SEM) for data analysis. Research results show that service, product and price all have a significant positive impact on customer trust, among which the impact of service is the most prominent; in contrast, promotion has a significant negative impact on customer trust, while convenience does not have a significant effect on customer trust. In addition, customer trust has a significant positive impact on purchase intention. Overall, research findings show that effective O2O marketing does not depend on the equal use of all marketing dimensions, but rather on strategically prioritizing those that effectively enhance customer trust. This study provides valuable practical insights for O2O platform managers to help them build customer trust in a fiercely competitive market environment and promote the continuous purchasing behavior of Generation Z consumers.